A Novel Capacity Fade Model of Lithium-Ion Cells Considering the Influence of Stress. Issue 9 (17th September 2021) - Luo, Pengfei; Li, Peichao; Ma, Dezheng; Wang, Keyong; Zhang, Hengyun
Abstract : This paper presents a capacity fade model of lithium-ion cell based on electrochemical-thermal-mechanical coupling, which incorporates the effect of stress on the capacity fade characteristic of lithium-ion cells. First, the electrochemical-thermal-mechanical coupling model of the cell is established and solved by COMSOL Multiphysics. Herein, the temperature-dependent dynamic parameters are introduced to more accurately describe the multi-field coupling feature of the cell during the operation. And the voltage, current, and stress distribution of the cell are obtained. Second, the lithium-ion loss due to the re-/formation of solid electrolyte interphase (SEI) is simulated and compared with the experiment in the literature. Next, the dependence of capacity characteristics on stress distribution is investigated in detail based on the presented model. We find that the electrochemical-thermal-mechanical coupling model has a higher side reaction rate than the classic electrochemical-thermal coupling model. Finally, the cell subject to external normal loads is modeled. The numerical results indicate that the tensile stress inhibits the side reaction, while the compressive stress promotes it. The findings in this paper are of benefit to understand the underlying mechanism of stress on the capacity fade.